Strategic Management Implementation at Immanuel Senior High School, Batu City, East Java - Juan Lestari Paiki; Nur Khoiri; Ghufron Abdullah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to describe and analyse the implementation of strategic management at Immanuel High School, Batu City, based on the Wheelen and Hunger model, which includes environmental observation, strategy formulation, strategy implementation, and evaluation and control. This study aims to describe and analyse the implementation of strategic management at Immanuel High School, Batu City, based on the Wheelen and Hunger model, which includes environmental observation, strategy formulation, strategy implementation, and evaluation and control. This study used a qualitative approach with a single case study design. Data were obtained through in-depth interviews, observations, and documentation studies of purposively selected informants. Data were then analysed using the interactive model of Miles, Huberman, and Saldaña with triangulation of sources and techniques to ensure data credibility. The study shows that service differentiation through the boarding system, character development, and multicultural management are the school's main strengths in implementing strategic management. This strategy is supported by the 3 Goods vision, which is internalised in all school programs and reinforced through a tiered evaluation mechanism. However, weaknesses remain, such as the lack of a standardised alum tracer study system and formal data-based environmental mapping. Strategic management has been integrated and effective in supporting school sustainability and the management of diverse students. This study confirms that integrating institutional values with strategic management practices is a crucial factor in building a school's competitive advantage.